2016
DOI: 10.1016/j.brainres.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of the ventral midline thalamus produce deficits in reversal learning and attention on an odor texture set shifting task

Abstract: The nucleus reuniens (RE) of the ventral midline thalamus in strongly reciprocally connected with the hippocampus (HF) and the medial prefrontal cortex (mPFC) and has been shown to mediate the transfer of information between these structures. It has become increasingly well established that RE serves a critical role in mnemonic tasks requiring the interaction of the HF and mPFC, but not tasks relying solely on the HF. Very few studies have addressed the independent actions of RE on prefrontal executive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 87 publications
1
21
0
Order By: Relevance
“…The fact that the RE is critically involved in extinction learning and recall is in line with previous work demonstrating the importance of the midline thalamus in both memory and emotion 23 25 , 32 35 . Importantly, a recent study demonstrated that the RE is important for maintaining the specificity of contextual fear memory 25 .…”
Section: Discussionsupporting
confidence: 90%
“…The fact that the RE is critically involved in extinction learning and recall is in line with previous work demonstrating the importance of the midline thalamus in both memory and emotion 23 25 , 32 35 . Importantly, a recent study demonstrated that the RE is important for maintaining the specificity of contextual fear memory 25 .…”
Section: Discussionsupporting
confidence: 90%
“…In essence, RE inactivation not only altered working memory and spatial perseveration but may have disrupted learned response strategies. In like fashion, we recently found that RE lesions not only altered behavioral flexibility but impaired rule abstraction, or the ability to use previously learned rule/response strategies to guide responses to new sensory stimuli (Linley et al, ).…”
Section: Discussionmentioning
confidence: 91%
“…Premature responding is viewed as a failure of impulse control and is seen with lesions of the infralimbic cortex on the 5‐CSRTT task (Chudasama et al, 2003). Finally, we recently described deficits in attention and reversal learning (a measure of behavioral flexibility) on an attentional set shifting task in RE lesioned rats (Linley et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, such spatial working memory tasks are dependent upon both the HC and ACC (Floresco et al, 1997;Izaki et al, 2000;Lee and Kesner, 2003;Churchwell et al, 2010), suggesting that RE-based interactions are integral to proper working memory function. Additionally, RE inactivation also impairs behavioral flexibility leading to perseveration in win-shift tasks (Viena et al, 2018) and an inability to generalize response strategies between contexts (Linley et al, 2016), which indicates a broader role in cognition for RE-based interactions. Although the current study involved a completely different task, it is conceivable that these same connections could mediate interactions in the opposite direction during remote recall.…”
Section: Discussionmentioning
confidence: 99%